Proses Berpikir Nabi Ibrahim as. Melalui Dialog dengan Tuhan dalam al-Qur’an - Syahputra, Afrizal El Adzim (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
Thinking and dialogue is an inseparable part of life. Various studies about the Prophet Ibrahim as. have been found, but the process of deepening related to thinking process through the dialogue of Prophet Ibrahim as. to Allah Swt is still limited to be discovered. This article is structured to reveal the way of thinking of Prophet Ibrahim as. in his efforts to dialogue with Allah Swt. This paper was prepared using the literature research method, which in this case uses the Qur'an as a primary reference and books, commentaries, and soft ware applications as a secondary reference source. The results show that the dialogue carried out by Prophet Ibrahim as. involves a process of critical thinking, rational thinking, accompanied by curiosity and based on faith and devotion to Allah Swt. Prophet Ibrahim as. who had previously been at the level of